Profiling Geoguides at Stong Geopark: Enhancing Local Expertise for Sustainable Ecotourism - Syerina Azlin Md Nasir; AN NUR NABILA ISMAIL; Wan Marhaini Wan Omar; Dana Anak Badang; Razaidi Shah A Kadir (Information Management and Business Review, 2024)
Stong Geopark is a prominent natural attraction site in Kelantan, characterized by its rich biodiversity and variety of species, catering to diverse visitor interests such as wildlife enthusiasts and tourists. Geoguides play a vital role in helping visitors comprehend the significance of the geopark's geological features, the interconnectedness of the ecosystem, and the knowledge of indigenous communities. However, the tourism industry faces challenges in meeting the requirements for various forms of tourism services, including geoguiding. This study aims to profile the geoguides at Stong Geopark and better understand their areas of expertise. The research employs a quantitative approach, surveying 39 geoguides, to provide a comprehensive profile. The findings reveal three distinct clusters of geoguides' areas of expertise: Cluster 1 - Nature and Adventure, Cluster 2 - Nature, and Cluster 3 - Adventure. The study also highlights the need for the majority of geoguides to receive additional training in English communication skills and continuous professional development courses. Overall, this study offers valuable insights into the profiles of geoguides at Stong Geopark, emphasizing the importance of supporting and developing local geoguides' expertise to enhance the effectiveness of geopark management and visitor satisfaction. Furthermore, the study provides a spatial understanding of Stong Geopark by highlighting the locations of active geoguides in relation to the distribution of geosites. The findings can inform policymakers, tourism authorities, and geopark management in developing targeted strategies for capacity building and professionalization of geoguides, ultimately contributing to the sustainable development of Stong Geopark as a thriving ecotourism destination.